Body position control in o-soto-gari throws performed in competitive bouts - Levitsky, A. G.; Matveyev, D. A.; Potsipun, A. A.; Gaponova, E. Y. (Theory and Practice of Physical Culture, 2017)
The article considers findings of an experiment to clarify and perfect the o-soto-gari throw technique applied in training process versus that in the competitive bouts. To obtain basic data for the experiment, we analysed video replays of the top-ranking competitors and exemplary performance records of the o-soto-gari throw technique performed by highly-skilled martial artists available on youtube.com, plus video records of the 18-23 year-old male athletes, with the video records analysed at the replay rate of 0.25 of the standard one. The snapshots of the opponents` support foot hooking moments were cut out by Print Screen command and processed by the Paintbrush toolkit. The trunk control angles were modelled by the straight line followed by the relevant geometric plotting to model the opponent`s body positions by a hypotenuse of a right-angled triangle. Ratios of the sides and angles of the right triangle were used to compute the body angle in every snapshot. It was found that the angle of trunk bent in the competitive bouts was significantly higher than in the training bouts with standing throws. This regularity may be interpreted as indicative of the role of the attacking fighter`s body centre of gravity (BSG) control in a real competitive bout. In this context we offer special sets of exercises that need to be introduced in the education and training process to develop the BSG control skills. The study data and analyses may be beneficial for martial artists, coaches and sport researchers active in martial arts.